2021
DOI: 10.3389/fcell.2021.605977
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lymph-Node Metastasis in Cancers Using Differentially Expressed mRNA and Non-coding RNA Signatures

Abstract: Accurate prediction of lymph-node metastasis in cancers is pivotal for the next targeted clinical interventions that allow favorable prognosis for patients. Different molecular profiles (mRNA and non-coding RNAs) have been widely used to establish classifiers for cancer prediction (e.g., tumor origin, cancerous or non-cancerous state, cancer subtype). However, few studies focus on lymphatic metastasis evaluation using these profiles, and the performance of classifiers based on different profiles has also not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We also compared the performance of our method with that of Zhang’s method [ 8 ] using the same data sets and the same SVM model. Among the seven types of cancer used in our study, comparison was made for four types of cancer because the four cancer types are common to both studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compared the performance of our method with that of Zhang’s method [ 8 ] using the same data sets and the same SVM model. Among the seven types of cancer used in our study, comparison was made for four types of cancer because the four cancer types are common to both studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the study of Okugawa et al [ 7 ] suggested that the expression of KiSS1 is closely related to lymph node metastasis in colorectal cancer. Zhang et al [ 8 ] predicted lymph node metastasis using differentially expressed mRNAs and noncoding RNAs. Dihge et al predicted lymph node metastasis using gene expressions combined with clinicopathological characteristics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16], proposed a SVM classifiers based on various features selection to forecast lymphatic metastasis in a range of malignancies. Such classifiers were applied to identify differentially expressed signatures in lymph node metastatic and non-metastatic cancer groups.…”
Section: Related Workmentioning
confidence: 99%